Financial Contagion of the Russian Economy: Intersectoral Aspect - А. О. Ovcharov; A. M. Terekhov (Финансы: теория и практика)
The study’s relevance is due to the need to identify the scale and channels of the spread of crises in the economy based on the use of the financial contagion methodology. Understanding the mechanism of spreading financial contagion from one industry to another can help develop anti-crisis measures and ensure stable economic indicators. The purpose of the study is to assess the intersectoral financial contagion in the Russian economy during the spread of the coronacrisis, as well as to correlate the estimates obtained with the actual incidence of COVID‑19 in the Russian Federation. The novelty of the research lies in the development of the methodology of financial contagion and its use in relation to sectors of the Russian economy, where they are considered transmitters and/or receivers of financial contagion. The methodology of advanced correlation analysis was used — the Forbes-Rigobon sliding test was implemented, which made it possible to assess the scale and intensity of financial contagion in the Russian economy. We used high-frequency data on 8 MICEX industry indices and on the incidence of COVID‑19 in the period 2020–2021. The result was quantitative assessments of financial contagion, which showed that such industries as metallurgy, oil and gas sector, consumer sector, electric power industry had the highest susceptibility to financial contagion. Telecommunications, the financial sector, chemicals and petrochemicals, and transport have demonstrated resistance to the pandemic shock. The most powerful transmitters of financial contagion were the electric power industry, metallurgy, transport, and the financial sector. In general, the financial contagion in 2020–2021 between the sectors of the Russian economy spread unevenly, in some cases and in certain periods, the ups and downs of financial infectivity went in parallel with the ups and downs of the real incidence of COVID‑19. The main conclusion was that during the pandemic, financial contagion spread with varying intensity, and individual industries manifested themselves either as receivers or transmitters of financial contagion. At the same time, there was no large-scale financial infection of the sectors of the Russian economy.